(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
This review presents a systematic analysis of biomarkers of rheumatoid arthritis (RA) activity, focusing on their prognostic and clinical relevance. The work characterizes classical inflammatory indicators (CRP, ESR), immunological markers (rheumatoid factor, anti-CCP, anti-MCV), cytokine profiles (IL-6, TNF-α, IL-17, IFN-γ), as well as molecular predictors including anti-CarP, carbamylated proteins, microRNAs (miR-146a, miR-155), genetic alleles (HLA-DRB1*04:01, PTPN22), and proteomic panels. Clinical data on over 15 key multi-omics predictors of therapeutic efficacy with methotrexate, tocilizumab, JAK inhibitors, and leflunomide are analyzed. Special attention is paid to the sensitivity and specificity of biomarkers in the assessment of DAS28, CDAI, and radiographic progression according to the Sharp/van der Heijde method. A direct association was found between IL-6 levels >30 pg/mL and active disease phase and erosion risk, as well as the role of anti-CCP2 titers >60 U/mL in predicting a destructive phenotype. A multidisciplinary synthesis of data from over 100 domestic and international sources published between 2007 and 2025, including meta-analyses, population-based cohort studies, and EULAR/ACR recommendations, is presented. The review critically evaluates stratification approaches based on biomarker platforms and their potential integration into clinical algorithms for personalized RA therapy.